2015
DOI: 10.14260/jemds/2015/2555
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Aetiology and Pattern of Mandibular Fractures in Pondicherry

Abstract: BACKGROUNDThe mandible is the second most commonly fractured part of the maxillofacial region after nasal bones. The incidence, etiology and pattern of mandibular fractures vary considerably among the different study population, there is a need to evaluate aspects of mandibular trauma in Pondicherry. This study was undertaken to evaluate the results of mandibular fractures treated in a population of Pondicherry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…About 48.9% of fracture patients in this study were 21-30 years old. This incidence is similar to estimates by Ragupathy and Pasupathy 10 . This could be because people in this age range are in the most active period of life and may be exposed to more dangerous situations that are more likely to result in accidents.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…About 48.9% of fracture patients in this study were 21-30 years old. This incidence is similar to estimates by Ragupathy and Pasupathy 10 . This could be because people in this age range are in the most active period of life and may be exposed to more dangerous situations that are more likely to result in accidents.…”
Section: Discussionsupporting
confidence: 91%
“…Data from different countries show large variations in fracture location site. Adebayo et al 26 reported the body of the mandible as the most prominent site, while Ragupathy and Pasupathy 10 and Țenţ et al 27 reported the condyle as the most frequent fracture site. In our study, the mandible body was the second most frequent fracture site.…”
Section: Discussionmentioning
confidence: 99%